Behçet’s Disease Diagnosed with a Multidisciplinary Approach in Pregnancy - Ömer DEMİR; Gizem ÖMEROĞLU DEMİR (Bezmiâlem Science)
Behçet’s disease (BD) is a disease that is characterized by recurrent oral aphthae and has various involvements especially in eye, skin and vascular structures. It was presented to the modern medical community by Hulusi Behçet in 1937. Although the prevalence of BD varies according to the population, it is mostly diagnosed in Türkiye. BD in patients with recurrent oral aphthae (at least three times in one year) plus two of the following clinical features: recurrent genital aphthae, eye lesions, skin lesions and a positive pathergy test. In the literature, data on BD diagnosed during pregnancy could not be reached. Our case was referred to the dentist at the 17th week of her pregnancy because of the wounds in her mouth. Then, after evaluation with a multidisciplinary approach, BD was diagnosed and treatment was started. In the literature, the effect of pregnancy on the disease or the effect of the disease on pregnancy has been investigated. Our case is the first in the literature to be diagnosed during pregnancy, a period when the disease is generally in remission.